Investigating The Drivers In Selecting Third Party Logistics (3PL) Provider: A Case Study From Indonesian Manufacturing Industry - Ferry Jie; Suci Dewi Ayurarasati; Ilyas Masudin; Dian Palupi Restuputri (International Journal of Supply Chain Management, 2020)
Logistics activities have become much concerned by many companies in term of an effective and efficient selection of Third-Party Logistics (3PL) provider. The use of 3PL providers and its effects to the customer satisfaction is mostly discussed in the case of manufacturing industry considering information technology variable, but the inclusion of trust as moderating variable between customer loyalty and customer satisfaction is limited. This article aims to identify the factors considered by Indonesian companies in selecting 3PL. Respondents of this research are managers of logistics or persons in charge of logistics activities. Structural Equation Modeling (SEM) is used to elaborate the relationship between factors affecting 3PL selection decision. The results indicate that Information Technology (IT) usage, service quality, trust and customer satisfaction are the factors affecting the companies to select a 3PL provider. Other results also show that there is a significant relationship between those factors.